Ethnobotanical knowledge of High School students about medicinal plants in Maranguape-Ceará (Research, Society and Development, 2021)
Plants have been used as medicines since antiquity and an ethnobotany seeks to understand how the population uses these plants. Therefore, the study aimed to verify the ethnobotanical knowledge of high school students from state public schools in Maranguape-CE about medicinal plants. The exploratory and descriptive study with a qualitative and quantitative approach was carried out through the application of semi-structured questionnaires to 188 high school students, on socioeconomic and ethnobotanical aspects. There was a predominance of females (51%) and an age range of 14 to 20 years. Students have large, low-income families. The majority (99%) believe in the power of medicinal plants, but prefer synthetics drugs (53%). 34 species were cited. The predominant method of preparation was tea (75.59%). The part of the plant most cited was the leaf (78.82%). The most cited therapeutic indications were related to diseases of the respiratory system (16), digestive system (11) and circulatory system (11). 41.24% have their own cultivation. Knowledge was obtained mainly from family members (82.45%). It is concluded that students have a simplified concept of medicinal plants, but they know and use medicinal plants. The subject of medicinal plants is little studied in schools and the greatest source of information is family members.